Evaluation of Subjects Experiencing Allergic Reactions to Non-Steroidal Anti-Inflammatory Drugs: Clinical Characteristics and Drugs Involved - Pérez-Sánchez, Natalia; Doña, Inmaculada; Bogas, Gador; Salas, María; Testera, Almudena; Cornejo-García, José A.; Torres, María J. (Frontiers in Pharmacology, 2020)
Non-steroidal anti-inflammatory drugs (NSAIDs), the most commonly prescribed and consumed medicines worldwide, are the main triggers of drug hypersensitivity reactions (DHRs). The underlying mechanisms of NSAID-DHRs may be related to COX-1 inhibition (cross-hypersensitivity reactions, CRs) or to immunological recognition (selective reactions, SRs), being the latter remarkably less studied. SRs include those usually appearing within the first hour after drug intake (single-NSAID-induced urticaria/angioedema or anaphylaxis, SNIUAA), and those usually occurring more than 24 hours after (single-NSAID-induced delayed reactions, SNIDR). We have evaluated the largest series of patients with SRs, analysing the number of episodes and drugs involved, the latency for reaction onset, the clinical entities, among other variables, as well as the value of available diagnostic methods. Globally, pyrazolones and arylpropionics were the most frequent culprits (39.3% and 37.3%, respectively). Pyrazolones were the most frequent triggers in SNIUAA and arylpropionics in SNIDR. Urticaria was the most common clinical entity in SNIUAA (42.4%) followed by anaphylaxis (33.3%); whereas SNIDR induced mostly fixed drug eruption (41.1%) and maculopapular exanthema (32.6%). The percentage of patients diagnosed by clinical history was higher in SNIUAA compared with SNIDR (62.7% versus 35.3%, p=0.00015), whereas the percentage of those diagnosed by skin tests was higher in SNIDR than in SNIUAA (47.1% versus 22.8%, p=0.00015). Drug provocation test with the culprit was performed in 67 SNIUAA (14.5%) and in 9 SNIDR (17.6%) patients. Our results may be of interest not only for allergologists but also for other clinicians dealing with these drugs, and can be useful for the correct identification of subjects experiencing DHRs to NSAIDs, and for avoiding mislabeling. Moreover, as NSAIDs are highly consumed worldwide, our results may be of interest for evaluating other populations exposed to these drugs.